Comparison of Outcomes with Triple-Regimen versus Double-Regimen Transarterial Chemoembolization - Smolock, Amanda R.; Deochand, Osmani; Rilling, William S.; Patel, Parag J.; Hohenwalter, Eric J.; White, Sarah B.; Scheidt, Matthew J. (Digestive Disease Interventions, 2022)
We sought to evaluate differences in outcomes between double versus triple transarterial chemoembolization (TACE). TACEs over a 1-year period were retrospectively reviewed and divided into two groups: double and triple. Imaging response and complications were made on a per-procedure basis. Student's t-test was used to calculate differences in continuous variables, and chi-square test was used to calculate differences in categorical values.Overall tumor response was similar between the two groups, and there were no significant differences in complications between groups. Outcomes are similar between double and triple conventional TACE, suggesting that adding a third drug may only contribute to cost.
Keywords: TACE; chemoembolization; regimen; dual therapy; triple therapy